Strains of the crown gall pathogen, Agrobacterium tumefaciens, and their biological control in South Africa - Van Zyl, F. G. H. (Frederik Gerhardus Heremias) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.)--Stellenbosch University, 1989.